Effects Of Mind Maps Teaching Approaches And Gender On Jordanian 7Th Graders’ Rational Number Achievement And Creative Thinking - Ayed Tbaishat, Abeer Yaseen (2023)
The purpose of this study was to determine the effect of mind maps and gender on rational number achievement and creative thinking among Jordanian seventh-grade students. The researcher used a quasi-factorial design (3x2) approach that was supported by qualitative data. To achieve the study’s objectives, four instruments were used, including the Rational Number Achievement Test (RNAT), the Torrance Test for Creative Thinking (TTCT), a questionnaire to assess students’ attitudes toward teaching methods, and an interview protocol for teachers. The researcher used the tools on a purposive sample of seventh-grade students in Irbid Governorate, which included (120) students divided into three groups: 60 female students and 60 male students. The control group is taught conventionally, while the first experimental group is taught with paper mind maps method and the second experimental group with digital mind maps methods. Two-way analysis of variance (ANOVA) and two-way analysis of covariance (ANCOVA) were used to analyze the data. The results of the two-way ANOVA analysis indicated that the teaching method (CM, PMM, or DMM) had a significant main effect on achievement in rational number among 7th-grade students. Students who were taught using the DMM improved more in Post Achievement in Rational Number than students who were taught using the PMM and CM.